High-performance hybrid supercapacitor with electrochemically exfoliated graphene oxide incorporated NiCo2O4 in aqueous and non-aqueous electrolytes. (June 2022) - Pappu, Samhita; Anandan, Srinivasan; Rao, Tata N.; Martha, Surendra K.; Bulusu, Sarada V.
Abstract: Hydrothermal approach is employed to synthesize electrochemically exfoliated graphene oxide (EGO) integrated NiCo2 O4 micro-flowers with nano petals. Specific capacity of 59 mAh g −1 (530 F g −1 ) is achieved by the optimized weight percentage of EGO in NiCo2 O4 with long cyclic stability over 10, 000 cycles. Detailed analysis on charge-storage properties of NiCo2 O4 –EGO composite reveals individual capacitive and diffusive contributions at various scan rates. An asymmetric supercapacitor device is fabricated with EGO incorporated NiCo2 O4 composite material and commercial YP-50F carbon as positive and negative electrodes in 1 M TEABF4 acetonitrile organic electrolyte for the first time. The device delivers promising electrochemical performance with energy and power densities of 37.8 Wh kg −1 and 1350 W kg −1 . Present work suggests an eco-friendly synthesis of EGO and provides a cost-effective facile approach for improving the overall electronic conductivity and cyclic stability of NiCo2 O4 and other similar metal oxide materials for high-performance supercapacitors. Graphical abstract: Unlabelled Image Highlights: NiCo2 O4 -EGO as positive electrode for hybrid supercapacitor Asymmetric device fabrication in aqueous and non-aqueous media Wide electrochemical window of 2.7 V High energy density of 37.8 Wh kg −1 at 1350 W kg −1 98% capacitance retention for 10, 000 cycles